PACAP ameliorates fertility in obese male mice via PKA/CREB pathway‐dependent Sirt1 activation and p53 deacetylation. Issue 10 (11th March 2020) - Yan, Qiuxia; Huang, Hongke; Lu, Shiyin; Ou, Biqian; Feng, Jia; Shan, Wailan; Li, Huixian; Wang, Zixian; Hong, An; Ma, Yi
Abstract: Obesity is strongly linked to male infertility. Testicular spermatogenic cell apoptosis plays an important role in obesity‐related male infertility. Pituitary adenylate cyclase‐activating peptide (PACAP) has been recently shown to exhibit antiapoptotic and antidiabetic effects. However, the effects of PACAP on obesity‐related male infertility remain unknown. The purpose of the current study is to explore the role of PACAP in obesity‐related male infertility. Here, C57BL/6 male mice were fed with a high‐fat diet to induce obesity and then treated with PACAP. PACAP treatment ameliorated obesity characteristics, including body weight, epididymal adipose weight, testes/body weight, serum lipids levels, and reproductive hormone levels in vivo. Additionally, PACAP was shown to improve the reproductive function of the obese mice, which was characterized by improved testis morphology, sperm parameters, acrosome reaction, and embryo quality after in vitro fertilization via silent information regulator 1 (Sirt1) activation and p53 deacetylation. These beneficial effects of PACAP were abolished in obese mice with testis‐specific knockdown of Sirt1. The mechanism studies showed that PACAP selectively binds to the PAC1 receptor to attenuate palmitic acid‐induced mouse spermatogenic cell (GC‐1) apoptosis via the PKA/CREB/Sirt1/p53 pathway. However, this mechanism was inhibited in GC‐1 cells lacking Sirt1. Finally, human semen studies showed that the decline in sperm quality in obese infertile men was partly due to Sirt1 downregulation and p53 acetylation. Our data suggest that PACAP could ameliorate fertility in obese male mice and may be a promising candidate drug for obesity‐induced male infertility. Abstract : Obesity can cause male infertility. PACAP could ameliorate fertility in obese male mice via PKA/CREB pathway‐dependent Sirt1 activation and p53 deacetylation and may be a promising candidate drug for obesity‐induced male infertility.